1995
DOI: 10.1007/bf00298376
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacteroides fragilis in clinical specimens by polymerase chain reaction amplification of the neuraminidase gene

Abstract: The polymerase chain reaction (PCR) was used in an attempt to detect Bacteroides fragilis by amplifying a segment of the gene encoding B. fragilis neuraminidase. Forty-five reference strains representing 45 species and 113 clinical isolates were tested. Only B. fragilis was PCR positive, except for Bacteroides merdae ATCC 43184, which gave a band by ethidium bromide staining that showed no signal by Southern hybridization. Using a protocol that employed DNA extraction by Sepa Gene kit and a highly sensitive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
3
19
2
2
Order By: Relevance
“…A segment of the toxin B gene was amplified by using primer NK104 (sequence, 5Ј-GTGTAGCAATGAAAGTCCAAGTTTACGC-3Ј; positions 2945 to 2972) (4) and primer NK105 (sequence, 5Ј-CACTTAGCTCTTTGATTGCTGCACC T-3Ј; positions 3123 to 3148) (4), which were derived from the nonrepeating sequence of the C. difficile toxin B gene. The specificity of the PCR product with primer set NK104-NK105 was confirmed by Southern blot analysis as described previously (10). Probe NK106 (sequence, 5Ј-GACTTACTTCCTACATTATCT GAAGG-3Ј; positions 3058 to 3083) (4) was used and was 3Ј end labeled with digoxigenin with a digoxigenin labeling kit (Boehringer Mannheim, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A segment of the toxin B gene was amplified by using primer NK104 (sequence, 5Ј-GTGTAGCAATGAAAGTCCAAGTTTACGC-3Ј; positions 2945 to 2972) (4) and primer NK105 (sequence, 5Ј-CACTTAGCTCTTTGATTGCTGCACC T-3Ј; positions 3123 to 3148) (4), which were derived from the nonrepeating sequence of the C. difficile toxin B gene. The specificity of the PCR product with primer set NK104-NK105 was confirmed by Southern blot analysis as described previously (10). Probe NK106 (sequence, 5Ј-GACTTACTTCCTACATTATCT GAAGG-3Ј; positions 3058 to 3083) (4) was used and was 3Ј end labeled with digoxigenin with a digoxigenin labeling kit (Boehringer Mannheim, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification of the neuraminidase, nanH, and glutamine synthase genes allowed direct detection of B. fragilis from clinical specimens containing other aerobic and anaerobic bacteria (Yamashita et al, 1994;Jotwani et al, 1995). It was shown that the presence of a specific PCR amplified nanH product completely correlated with positive cultures for B. fragilis.…”
Section: Molecular Approachesmentioning
confidence: 99%
“…In the past decade, molecular genetics-based techniques, including hybridization assays using a DNA probe or an RNA probe (10,17,30) and peR amplification (15,18,37), have been developed for the specific detection of B. fragilis, and some of these techniques have been shown to have adequate sensitivity and speci-Abbreviations: Ala-tRNA, alanyl transfer RNA; ATCC, American Type Culture Collection; Ile-tRNA, isoleucyl transfer RNA; ITS, internal transcribed spacer; JCM, Japanese Collection of Microorganisms; NCTC, National Collection of Type Cultures; PCR, polymerase chain reaction; RFLP, restriction fragment length polymorphism; rRNA, ribosomal RNA; rrn, ribosomal RNA operon.…”
mentioning
confidence: 99%